Jenis dan Peranan Parasitoid dalam Mengendalikan Populasi Lalat Buah (Bactrocera dorsalis Complex.) (Diptera: Tephritidae) yang Menyerang Buah Mangga (Mangifera indica L) di Kabupaten Buleleng - I WAYAN SUSILA; I WAYAN SUPARTHA (Agrotrop : Journal on Agriculture Science, 2020)
The Role of parasitoid in controlling the population of fruit flies (Bactrocera dorsalis Complex.) (Diptera: Tephritidae) who attacked mangoes (Mangifera indica L) in Buleleng Regency. Thisresearch was conducted with the aim of knowing the role of parasitoids in controlling the population of fruit flies (Bactrocera dorsalis Complex.) (Diptera: Tephritidae) on mango plants (Mangifera indica L.) in Buleleng Regency. Field research was carried out at the Buleleng mango plantations while laboratory research was carried out at the Integrated Pest Management and Plant Disease Laboratory from April to July 2019.Field research was carried out at the Buleleng mango plantations while laboratory research was carried out at the Integrated Pest Management laboratory and was carried out from April to July 2019. Determination of the location of sampling is done diagonally and fruits infested larvae was taken purposively. The results showed that there were three species of fruit flies that attacked mango in Buleleng Regency, namely B. carambolae, B. papayae and B. occipitalis with an abundance of B. carambolae 39.3%, B. papayae 64.4% and B. occipitalis 0.3% and found three types of parasitoids namely Fopius sp, Diachasmimorpha sp. and Opius sp. The role of parasitoids in controlling fruit flies is still low when viewed from the parasitization rate of the three parasitoids namely Fopius sp. (2,24%), Diachasmimorpha sp. (1,9%), and Opius sp. (0,46%).